Reperfusion injury or cytokine storm? Utilizing plasmapheresis in severe trauma-induced multiorgan failure: a case report - Gun Woo Kim; Suyeong Hwang; Kyoung Hoon Lim; Sung Hoon Cho (Journal of Trauma and Injury)
Reperfusion injury can cause tissue damage due to ischemia, with severe cases potentially resulting in multiorgan failure. Cytokine storm, a life-threatening systemic inflammatory state characterized by elevated levels of circulating cytokines and hyperactive immune cells, can also lead to tissue damage and multiorgan failure. Reperfusion injury and cytokine storm sometimes exhibit similar clinical features, necessitating specific treatment in severe cases. A 31-year-old man sustained a stab wound to his left knee. Computed tomography angiography and surgical exploration revealed a transection of the left popliteal artery and vein. Both vessels were revascularized via end-to-end anastomosis approximately 3 hours after the injury. On postoperative day 2, marked increases were observed in levels of aspartate aminotransferase (8,600 U/L), alanine transaminase (6,690 U/L), creatine phosphokinase (26,817 U/L), and lactate dehydrogenase (7,398 U/L) levels. Elevated levels of interleukin 6 (178 pg/mL) and ferritin (41,079 ng/mL) were also noted. Given the possibility of either reperfusion injury or cytokine storm, plasmapheresis was initiated. Following two rounds of plasmapheresis, the patient’s condition rapidly improved, and he was discharged without complications. Reperfusion injury can arise when a target blood vessel is revascularized, particularly during severe stages of ischemia. Cytokine storm represents a life-threatening systemic inflammatory state characterized by high levels of circulating cytokines and overactive immune cells. Both reperfusion injury and cytokine storm can cause systemic inflammation and multiorgan failure. These two conditions may exhibit similar clinical features, necessitating supportive care primarily to prevent organ dysfunction. However, plasmapheresis may represent an effective treatment option in cases of severe progression.